Research Networks: a fundamental value-added for scientific communication (2013)
This edition of Universitas Psychologica has a special value because it is the result of a collaborative work with a research group from the Universidad de La Frontera led by Ricardo Perez Luco, Jaime Alfaro and Beatriz Paes from Chile, who organized the “First International Seminar of Juvenile Justice. Be and Ought to be of the public policy” a meeting that brought together world leading researchers in order to investigate an emerging and critical problem in our societies, such as the juvenile justice. We accep their proposals after agreeing the compliance of our demands of peer review and think that we are a trusted international academic channel. The first 14 articles of this edition were the result of an exhaustive peer-review evaluation, which have guaranteed quality. We hope readers will recognize the building of the theme proposed. This edition contains articles from universities and institutions of Argentina, Brazil, Canada, Chile, Colombia, Costa Rica, The United States, Spain, Italy, France and Mexico. Moreover, I would like to mention the importance of our panorama section in which we are publishing interviews with world leading academics such as Professor Mario Bunge, one of the most influential living philosophers of our time (author of the Treaty of Philosophy 1974-1989 “one of the most ambitious projects of modern philosophy” and of numerous, influential and provocative books on multiple topics of the contemporary society); and recently with Kenneth Gergen, a theorist who has significantly substantiated the social constructivist psychology and critical perspectives associated with this. There are also interviews with psychologists who have made contributions to psychology, as Fernando González Rey. Universitas will continue publishing these types of articles for discussion and reflection, as well as a quality research, and we invite our readers and authors to evaluate the presentation of this kind of contributions. Wilson López López Editor